2021
DOI: 10.1186/s12909-021-02540-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of self and simulated patient assessments of first-year medical students’ Interpersonal and Communication Skills (ICS) during Objective Structured Clinical Examinations (OSCE)

Abstract: Background Interpersonal and communication skills (ICS) are important core competencies in medical education and certification. In this study, we identified self- and simulated patient (SP)-reported ratings of US first-year medical students’ ICS and the influence of age and gender on performance appraisal during the Objective-Structured Clinical Examination (OSCE). Methods OSCE participants, including 172 first-year medical students and 15 SPs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…To our knowledge, limited data exist on the relationship between examination scores or number of medical college admission test attempts and communication skills for medical students. A previous study reported a weak but significant correlation between academic examination scores undertaken over the first 2 years of medical school and subsequent OSCEs [ 28 ], which constitute an alternative approach for assessing student communication and interpersonal skills [ 40 ]. Our study failed to show any significant association between basic science multiple-choice examination scores and subsequent 4-HCS overall score.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, limited data exist on the relationship between examination scores or number of medical college admission test attempts and communication skills for medical students. A previous study reported a weak but significant correlation between academic examination scores undertaken over the first 2 years of medical school and subsequent OSCEs [ 28 ], which constitute an alternative approach for assessing student communication and interpersonal skills [ 40 ]. Our study failed to show any significant association between basic science multiple-choice examination scores and subsequent 4-HCS overall score.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that communication skills should not only be assessed from the student’s own point of view, but that structured external assessments such as the Objective Structured Clinical Examination (OSCE) [ 59 ] should also be employed. For decades, the OSCE has been used for multiple purposes during the training of nursing students, including training in communication skills [ 60 ]. However, recent research suggests that students’ perceptions of their communication skills often tend to coincide with those of external evaluators [ 51 , 60 ], and so both perspectives must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…For decades, the OSCE has been used for multiple purposes during the training of nursing students, including training in communication skills [ 60 ]. However, recent research suggests that students’ perceptions of their communication skills often tend to coincide with those of external evaluators [ 51 , 60 ], and so both perspectives must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In the published studies, the authors most often used the OSCE as a tool for assessing students’ competencies and for assessing the course itself [ 27 29 ]. Some authors also compare the exam results obtained by students during the assessment conducted by the examiner or the feelings of the simulated patient with the competencies perceived by students [ 30 , 31 ]. According to the trends in teaching in medical and pharmaceutical sciences, as part of such a comprehensive course as Pharmaceutical Care, we give up teaching methods in favor of activating methods [ 32 – 34 ].…”
Section: Discussionmentioning
confidence: 99%